The disadvantage of late-moulting by Mute Swans Cygnus olor - Perrins, C M; McCleery, R H (Wildfowl, 1995)
The weights of Mute Swans which have been caught in round-ups on the Fleet at Abbotsbury are examined. Those which have not yet started to moult are lighter than those which are already moulting and survive less well afterwards.